The First Molecular Genotyping of Naegleria fowleri Causing Primary Amebic Meningoencephalitis in Thailand With Epidemiology and Clinical Case Reviews - Soontrapa, Pannathat; Jitmuang, Anupop; Ruenchit, Pichet; Tiewcharoen, Supathra; Sarasombath, Patsharaporn T.; Rattanabannakit, Chatchawan (Frontiers in Cellular and Infection Microbiology, 2022)
Primary amebic meningoencephalitis (PAM) is a rare and fatal central nervous system infection caused by Naegleria fowleri, a free-living amoeba found in the environment. To now, eight pathogenic N. fowleri genotypes have been reported worldwide. We aimed to explore the genotypes of N. fowleri that cause primary amebic meningoencephalitis in Thailand. In 2021, the 17th PAM case was reported, and a retrospective literature search of PAM cases in Thailand from 1982 through April 2021 was performed. Phylogenetic and genotyping analyses of the two mitochondrial (12S rRNA and 16S rRNA) and nuclear (ITS1 and 5.8s rRNA) genes of N. fowleri were performed on four available clinical isolates. Based on the mitochondrial and nuclear genes, N. fowleri genotype T3 was found to cause PAM in 3 out of 4 cases. However, disagreement between the genotype based on the mitochondrial and nuclear genes was found in one of the PAM cases, in which the 12S rRNA locus suggested the causative genotype as T1, while the ITS1 implied genotype T4. The discrepancy between the mitochondrial and nuclear genome was previously observed, which suggests the possible horizontal gene transfer among N. fowleri species. Based on the ITS1 gene, two N. fowleri genotypes, T3 and T4, were found to be the genotypes causing PAM in this study. In addition, N. fowleri genotype T2 was previously reported in a traveler who was infected in Thailand. Thus, at least three genotypes (T2, T3, and T4) of N. fowleri are found to be associated with PAM in Thailand.